Poison arrows : North American Indian hunting and warfare - Jones, David E (University of Texas Press, 2007)
Biological warfare is a menacing twenty-first-century issue, but its origins extend to antiquity. While the recorded use of toxins in warfare in some ancient populations is rarely disputed (the use of arsenical smoke in China, which dates to at least 1000 BC, for example) the use of “poison arrows” and other deadly substances by Native American groups has been fraught with contradiction. At last revealing clear documentation to support these theories, anthropologist David Jones transforms the realm of ethnobotany in Poison Arrows. Examining evidence within the few extant descriptive accounts of Native American warfare, along with grooved arrowheads and clues from botanical knowledge, Jones builds a solid case to indicate widespread and very effective use of many types of toxins. He argues that various groups applied them to not only warfare but also to hunting, and even as an early form of insect extermination. Culling extensive ethnological, historical, and archaeological data, Jones provides a thoroughly comprehensive survey of the use of ethnobotanical and entomological compounds applied in wide-ranging ways, including homicide and suicide. Although many narratives from the contact period in North America deny such uses, Jones now offers conclusive documentation to prove otherwise. A groundbreaking study of a subject that has been long overlooked, Poison Arrows imparts an extraordinary new perspective to the history of warfare, weaponry, and deadly human ingenuity.